Visual Performance of Children with Amblyopia after 6 Weeks of Home-Based Dichoptic Visual Training - Piñero, David P.; Gil-Casas, Amparo; Hurtado-Ceña, Francisco J.; Molina-Martin, Ainhoa (Children (Basel), 2024)
Objectives: This study was aimed at analyzing the efficacy on the improvement of the visual function of a dichoptic online cloud-based platform for the treatment of amblyopia in anisometropic children. Methods: A quasi-experimental (pretest–post-test) study was conducted in 23 subjects with ages from 5 to 15 years old with anisometropic amblyopia combined with additional presence (2 subjects) or not (21 subjects) of microtropia. A total of 30 home-based training sessions of 30 min per session with Bynocs® platform were prescribed for 6 weeks. Results: Amblyopic eye logMAR visual acuity (VA) significantly improved from 0.28 ± 0.24 to 0.13 ± 0.20 after the 6-week treatment (p < 0.001). At baseline, 60.9% of participants had VA in amblyopic eye of 0.20 logMAR or worse, whereas this percentage decreased to 21.7% after treatment. Binocular function (BF) significantly improved from 2.82 ± 1.11 to 2.32 ± 0.94 (p < 0.001). Mean compliance was 92%, 87% and 93% at 2, 4 and 6 weeks of treatment, respectively. Conclusions: In conclusion, home-based dichoptic training with the digital platform evaluated is an effective method to improve amblyopic VA and stereoacuity in children with anisometropic amblyopia combined or not with microtropia.